An Examination of Curricula in Middle Eastern Journalism Schools In light of Suggested Model Curricula - Tahat, Khalaf; Self, Charles; Tahat, Zuhair (Jordan Journal of Social Sciences, 2020)
This study seeks to understand how journalism is taught in the Middle East. A basic questionnaire was developed to solicit such information to examine the curricula of 95 journalism programs in 13 countries of the Middle East. The study examines these curricula in hopes of developing a better understanding of the needs of journalism educators in one of the fastest growing areas of the world The data shows that about half of the journalism programs in the Middle East had been established within the last decade. It also finds that most of these programs were theoretically oriented with little attention to practical concepts. Internships are not a top priority at most schools. Admissions criteria are poorly articulated. Most programs do not have much interaction with media organizations or international partners. The data confirm much of what found in the literature. Scholars in the region say too much theory, and too little journalism practice is taught. The results show that there is a big gap between theoretical and practical concepts in most of Middle East journalism programs’ curricula. Most of these programs are theoretical oriented and do not pay much attention to the practical concepts.